Dietary Knowledge, Attitudes, Practices and their Association with Demographic Factors in Type 2 Diabetes Patients - Mohamad Fadzli, Nur Zarith Sufia; Shamsudin, Juliana (Jurnal Gizi dan Pangan, 2025)
The study aimed to assess dietary Knowledge, Attitude, And Practice (KAP) among Type 2 Diabetes Mellitus patients at Hospital Pakar USM (HPUSM), and their associations with demographic characteristics. The study used a cross-sectional design with a convenience sampling method, and the analysis included responses from 118 participants. Their dietary KAP and demographic characteristics were assessed using an adapted and translated questionnaire based on the ADA Diabetes Self-Management Assessment Research Tool (D-SMART) and the University of Michigan Diabetes Research and Training Centre’s KAP questionnaire. The questionnaire was translated and pilot-tested among 10% of the study population to ensure clarity and understanding. Minor adjustments were made based on participant feedback. The mean age of the 118 participants was 58.0±13.3 years, with 40.7% men and 59.3% women. The vast majority of participants possessed favourable attitudes (91.5%), good dietary knowledge (84.7%), and good practice (72.9%). Specifically, the mean scores for dietary knowledge, attitude, and practice were 41.8±9.39, 5.4±1.06, and 5.3±1.6, respectively. Bivariate analyses indicated significant associations between education level and knowledge (p=0.007) and attitude (p=0.009) but not practice (p=0.942). Multivariate Analysis of Variance (MANOVA) demonstrated a significant multivariate association between education level and the combined KAP scores, Pillai’s Trace=0.182, p=0.001. The remaining demographic variables were not significantly associated with the combined KAP scores in the multivariate model (p>0.05).The results of the study indicate that, despite the fact that the majority of participants had favourable dietary knowledge, attitudes, and practices, education level significantly influenced knowledge and attitude scores. This underscores the importance of providing ongoing and targeted dietary education, particularly for individuals with lower educational attainment, to facilitate more effective dietary management among those with Type 2 Diabetes Mellitus (T2DM).